Globicephala melas subsp. melas Traill 1809 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Globicephala melas subsp. melas Traill 1809 Globicephala melas subsp. melas Traill 1809, Nicholson's J. Nat. Philos. Chem. Arts, 22: 81. Type Locality: UK, Scotland, "in Scapay Bay, in Pomona, one of the Orkneys". Vernacular Names: North Atlantic Longfinned Pilot Whale. Synonyms: Globicephala melas subsp. globiceps (G. Cuvier 1812); Globicephala melas subsp. svineval Gray 1846. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 728, DOI: 10.5281/zenodo.7316519